A new mode for an on-line determination of Pyrocatechol, Resorcinol, and Pyrogallol in pure commercial samples using CFIA with homemade Ayah 3SBGRx3- 3D solar cell microphtometer analyzer. - S. TurkieAl-Awadie, Nagam; H. AlalooshAlamri, Malik (Iraqi Journal of Science, 2023)
A new, simple, accurate, fast and sensitive spectrophotometric method has beendeveloped for the analysis of Pyrocatechol, Resorcinol, and pyrogallolin purecommercial samples by continuous flow injection analysis. The method was based onthe oxidation of the organic compounds with Ce(IV)sulfate in acidic medium toformed a brown colored species which determined using homemade Ayah 3SBGR x3-3D solar cell flow injection microphotometer. Optimum conditions were obtainedusing a high intensity green light emitted diode as an irradiation sourceforPyrocatechol, Resorcinol, whileblue light emitted diode as an irradiation source forpyrogallol. The linear dynamic range for the instrument response versus Pyrocatechol,Resorcinol, and pyrogallol concentrationswere5-40mmol.L-1 while the L.O.D was of36.63, 17.17, and 41.61ng / sample respectively. The correlation coefficient (r) was0.9952, 0.9970, and 0.9960 while percentage linearity (r2%) was 99.05%, 99.41% and99.22%forPyrocatechol, Resorcinol, and pyrogallol respectively. RSD% for therepeatability (n=8,7, and 8) was 1.4%, 0.63%, 1.78% for the determination ofPyrocatechol, Resorcinol,andpyrogallol, respectively at concentration of 30 mmol.L-1.The method was applied successfully for the determination of three organiccompounds in purecommercial samples. A comparison was made between the newlydeveloped method and the classical method (UV-Vis spectrophotometry) at wavelength 492, 481, and 438 nm forPyrocatechol, Resorcinol and pyrogallolrespectivelyof analysis using the standard additions method via the use of paired t-test. It wasnoticed that there is no significant difference between two different methods foranalysis three different organic compounds; in addition to no significant difference inthe contribution of the Pyrocatechol, Resorcinol and pyrogallol to the oxidant reactionpath, at 95% confidence level.